Analysis of Discussions within the Chinese Society on China’s Position in World in the Context of Sino-American Relations Deterioration during the Pandemic Period - A. N. Karneev; A. S. Pyatachkova (Сравнительная политика, 2020)
During the pandemic, Sino-US relations have remarkably deteriorated. The institutionalization of such destructive practices as toughening rhetoric in the media and sanctions is becoming obvious. As the model of bilateral relations is now aimed at decoupling the degradation will continue. These trends inevitably affect the mood of the Chinese society. The article analyzes opinions on foreign policy in Chinese society in the context of Sino American relations within the pandemic period. The work is divided into two parts: the first assesses general trends in US-China relations. The second part traces the current trends in the modern ideological and political atmosphere in Chinese society. The episode with congratulations to the Chinese public from the American administration on the occasion of the 101st anniversary of the famous «May 4, 1919 movement» is analyzed as a case study. The research shows that this event received ambiguous and even opposite assessments: part of the society saw in it as an attempt to accuse China of the spread of coronavirus and the imposition of Western values. Another part emphasized M. Pottinger’s rather high level of spoken Chinese and noted that the very fact of congratulation can be viewed as a positive moment for bilateral relations. There were also positions combining both approaches. The case under consideration reveals the danger of decoupling initiated by the parties. The tension between the PRC and the United States leads to the fact that the partners are starting to interpret each other’s intentions as presumably hostile, even taking into account such a formally favorable occasion as congratulations on a significant historical date. Meanwhile, it seems that the presence of positive interpretations against the background of a general deterioration in bilateral relations also cannot be ignored. Although public opinion cannot be unambiguous and does not always directly influence specific political steps, it is important to take into account the full range of opinions for an objective and comprehensive analysis of Sino American relations.